Low cost and low carbon footprint bendable concrete - Soh, Jia Min (Nanyang Technological University, 2021)
Due to the unsustainable carbon pollution from the manufacture of concrete, researchers are investigating the possibility of using magnesium-silicate-hydrate (M-S-H) based cement as an alternative cementitious material to Portland cement (PC) to reduce this environmental problem. Despite being one of the most commonly used construction materials worldwide, concrete has poor tensile properties. Thus, Engineered Cementitious Composites (ECC) has emerged as a replacement to conventional concrete. ECC has strain-hardening properties which are govern by fiber, cement matrix and interface properties. This study focuses on the feasibility of using MSH-based cement with sand. Different proportion of silica sand and river sand were included in this study to reduce the cost of ECC while attaining desirable mechanical properties. The mechanical properties were investigated after 28 days of curing. It can be concluded that with the addition of silica sand and river sand in the composites, both composites demonstrated strain-hardening behaviour with multiple cracks observed and high compressive strength. Even though, the tensile strain-hardening capacity of the composites decreases as the sand/binder ratio increases, a composite with a higher sand/binder ratio also displayed relatively desirable mechanical properties.